Antiparkinsonian Efficacy of Guanosine in Rodent Models of Movement Disorder - Massari, Caio M.; López-Cano, Marc; Núñez, Fabiana; Fernández-Dueñas, Víctor; Tasca, Carla I.; Ciruela, Francisco (Frontiers in Pharmacology, 2017)
Guanosine (GUO) is a guanine-based purine nucleoside with important trophic functions and promising neuroprotective properties. Although the neuroprotective effects of GUO have been corroborated in cellular models of Parkinson’s disease (PD), its efficacy as an antiparkinsonian agent has not been fully explored in PD animal models. Accordingly, we evaluated the effectiveness of GUO in reversing motor impairments in several rodent movement disorder models, including catalepsy, tremor, and hemiparkinsonism. Our results showed that orally administered GUO antagonized reserpine-mediated catalepsy, reduced reserpine-induced tremulous jaw movements, and potentiated the number of contralateral rotations induced by L-3,4-dihydroxyphenylalanine (L-DOPA) in unilaterally 6-hydroxidopamine-lesioned rats. In addition, at 5 and 7.5 mg/kg, GUO inhibited L-DOPA-induced dyskinesia (LID) in rats chronically treated with a pro-dopaminergic agent. Overall, we describe the therapeutic potential of GUO, which may be effective not only for reversing parkinsonian motor impairments but also for reducing dyskinesia induced by treatment for PD.